Polytene Chromosome Banding Pattern three Drosophila species from Bangladesh (Bangladesh Journal of Zoology, 2024)
In this study, polytene chromosome maps of three Drosophila species (D. ananassae, D. bipectinata, and D. melanogaster) belonging to the melanogaster group were constructed based on their banding patterns obtained through analysis of images generated by aceto-orcein staining of salivary gland chromosomes. The nuclei of the salivary gland cells in each of the three Drosophila species contained six chromosome arms (X, 2L, 2R, 3L, 3R, and 4). The chromosomal inversion number and banding patterns of six chromosome arms were slightly changed among D. melanogaster, D. ananassae and D. bipectinata. Banding patterns were similar in D. melanogaster and D. ananassae. However, D. bipectinata polytene chromosome banding pattern were slightly different from that of D. melanogaster and D. ananassae. A significant banding difference was observed in the case of D. bipectinata. Chromosome number 4 was detected as a small chromosome among the Drosophila chromosomes. The species-specific polytene chromosome banding patterns can be valuable tools for chromosomal aberration detection. Thus, the results might provide a background to study their evolutionary history, genetic diversity, and phylogenetic relationships.Bangladesh J. Zool. 52(2): 253-261, 2024